Perlindungan Hukum bagi Konsumen terhadap Penjualan Makanan Kadaluwarsa yang Dijual di Internet - Made Krishnanda Arya Wiguna; I Gede Pasek Eka Wisanjaya (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to examine the legal protection of consumers against the sale of expired foods sold on the Internet as well as to find out what legal action can be taken by consumers for losses incurred by the entrepreneur. The study uses a method of normative law research, with an approach to both primary and secondary law sources. The results of the study show that the legal protection for consumers in sales activities is regulated in the Consumer Protection Act. The legal protection of consumers can be carried out through preventive protection and repressive protection. The legal protection of consumers does not always run as written in the rules, often there is a violation of consumer rights, which ends with the emergence of disputes between the entrepreneurs and consumers. The consumer may take legal action if he or she feels that any of his or her rights have been violated through the court or outside the court.